(untitled) (Journal of Veterinary Medicine and Animal Production, 2023)
Mish is traditional fermented milk that might be consumed alone or with the meals. Currently mish is produced by different dairy companies and stored in groceries for a period of 21 days (shelf life) in a condition, which might affect its microbiological load. This study aimed to evaluate and compare the effect of storage period on the microbiological load of mish collected from three different dairy companies (C1, C2 and C3). Ten samples of mish were collected from each company during day 2 and day 20 randomly from groceries for microbiological evaluation (total viable bacteria, coliform and yeast and mold counts). The microbiological analysis results showed that log total viable bacterial count (6.120) and coliform count (5.872) revealed non-significant (P>0.05) differences between those companies. The total viable bacteria and coliform showed log 6.090 and log 5.858 for mish samples collected during day 2 respectively, while the respective values were log 6.149 and 5.886 for mish samples during day 20. Yeast and mold counts showed highly significant differences (P<0.001) between mish producing companies, which recorded a mean of log 5.326. Also it increased from day 2 (log 5.034) to day 20 (log 5.619) during the storage periods. This study remarked that there were variations between and within mish producing companies in their microbial properties. This might be related to the variations of raw materials, the processing methods and the storage conditions in retailers. Hence this study recommended consumption of fresh mish, in addition the methods of its preservation should be considered